Plastic design of orthotropic circular plates - Kumar V. (My University, 2025)
Load carrying capacities of simply supported thin orthotropic circular plates subjected to axially symmetric loading are determined by plastic analysis using modified Tresca Yield Condition and its associated flow rules. Design charts for these loading conditions are constructed. An example is also given to explain the use of these charts for the design of a pressure vessel head.